Tomato Root Penetration in Soil Requires a Coaction between Ethylene and Auxin Signaling - Santisree, Parankusam; Nongmaithem, Sapana; Vasuki, Himabindu; Sreelakshmi, Yellamaraju; Ivanchenko, Maria G.; Sharma, Rameshwar (Plant physiology (Bethesda), 2011)
During seed germination, emerging roots display positive gravitropism and penetrate into the soil for nutrition and anchorage. Tomato (Solanum lycopersicum) seeds germinated in the presence of 1-methylcyclopropene (1-MCP), an inhibitor of ethylene action, failed to insert roots into Soilrite and grew in the air, forming loops. Time-lapse video imaging showed that 1-MCP-grown root tips retained positive gravitropism and made contact with the surface of Soilrite but failed to penetrate into the Soilrite. Time-course studies revealed that the effect of 1-MCP was most prominent when seed imbibition and germination were carried out in the continual presence of 1-MCP. Conversely, 1-MCP was ineffective when applied postgermination after penetration of roots in the Soilrite. Furthermore, treatment with 1-MCP caused a reduction in DRS::β-glucuronidase auxin-reporter activity and modified the expression of SIIAA3 and SIIAA9 transcripts, indicating interference with auxin signaling. The reduced ethylene perception mutant, Never-ripe, displayed decreased ability for root penetration, and the enhanced polar auxin transport mutant, polycotyledon, showed a nearly normal root penetration in the presence of 1-MCP, which could be reversed by application of auxin transport inhibitors. Our results indicate that during tomato seed germination, a coaction between ethylene and auxin is required for root penetration into the soil.